Sistem Pendukung Keputusan Penilaian Kesehatan Tanah Dengan Metode Simple Additive Weighting - Arief Kelik Nugroho; Ipung Permadi; Nofiyati Nofiyati; Sri Hayyu Naufal Ulfa (Politeknik Harapan Bersama, 2019)
Soil is the most crucial factor in the management of agriculture. To measure and monitor soil health status, soil health assessments can be undertaken in the management of agricultural land that aims to determine whether the land is being or will be used in an area in a healthy condition and can perform its functions properly. The results of soil health assessments can also be used as a reference for agricultural land managers to set planning targets and implementing systems to practice soil health management by reducing identified constraints, and assisting land managers in searching agricultural land. Comprehensive soil health assessments can be undertaken based on soil health indicators which consist physical, chemical, and biological properties of the soil. But there is no definite standard for assessing soil health comprehensively, and people who know and understand soil health indicators are still minimal. The number of indicators in soil health assessments can also make it difficult for experts to assess the health of the soil. Therefore, it is needed a Decision Support System of Soil Health Assessment Using Simple Additive Weighting Method so that with this application, it is expected to assist the community especially those involved in agriculture in assessing soil health easily, and quickly, and obtain land health status of an area based on predetermined soil health indicators.